2023
DOI: 10.1101/2023.01.27.525822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human aneuploid cells depend on the RAF/MEK/ERK pathway for overcoming increased DNA damage

Abstract: Aneuploidy is a hallmark of human cancer, yet the cellular mechanisms that allow cells to cope with aneuploidy-induced cellular stresses remain largely unknown. Such coping mechanisms may present cellular vulnerabilities that can be harnessed for targeting cancer cells. Here, we induced aneuploidy in non-transformed RPE1-hTERT cells and derived multiple stable clones with various degrees of chromosome imbalances. We performed an unbiased genomic profiling of 6 isogenic clones, using whole-exome and RNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 101 publications
1
9
0
Order By: Relevance
“…As cycling aneuploid cells upregulate the DDR both in comparison to euploid cells and to arrested aneuploid cells, we conclude that this is not a consequence of higher proliferative capability and/or driven by a small fraction of diploid cells present in the population. Importantly, the activation of DNA damage repair pathways in aneuploid cells is consistent with our recent findings in cancer 20 and untransformed cells 50 . We therefore hypothesized that higher expression of DNA damage repair genes would confer a growth advantage to the cells.…”
Section: Cycling Aneuploid Cells Display Increased Expression Of Dna ...supporting
confidence: 91%
“…As cycling aneuploid cells upregulate the DDR both in comparison to euploid cells and to arrested aneuploid cells, we conclude that this is not a consequence of higher proliferative capability and/or driven by a small fraction of diploid cells present in the population. Importantly, the activation of DNA damage repair pathways in aneuploid cells is consistent with our recent findings in cancer 20 and untransformed cells 50 . We therefore hypothesized that higher expression of DNA damage repair genes would confer a growth advantage to the cells.…”
Section: Cycling Aneuploid Cells Display Increased Expression Of Dna ...supporting
confidence: 91%
“…Since 7 gain in the presence of 10 loss is associated with decreased essentiality to chromosome 10 genes and increased essentiality to chromosome 7 genes, this suggests an evolutionary pressure to maintain 7 gain in the presence of 10 loss, consistent with an associated selective advantage. Furthermore, we analyzed a CRISPR screen of recently developed isogenic system of RPE1 cells molecularly engineered to have distinct single whole-chromosome trisomies 85 . The chromosome 10 genes that were essential in the near-diploid clone (RPE1-SS48) were significantly less essential in the clone with trisomy 7 (RPE1-SS6), but not in the clone with trisomy 8 (RPE1-SS119) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used CRISPR gene-knockdown essentiality screen data from DepMap 84 for our cell line essentiality analysis. Arm change event information for cell lines was taken from previous literature 85,98 . We then divided CNS cancer cell lines into two groups based on arm-level copy-number events.…”
Section: Methodsmentioning
confidence: 99%
“…To validate these as compensated genes, we examined gene expression and calculated gene compensation scores in isogenic RPE-1 clones with gained chromosomes (either chromosome 7 or a combination of chromosome 7 and 22; or 8, 9 and 18; for 7, 10 and 7 compensated genes Fig. S2e ) 10,37 . We confirmed that the compensated genes residing on the respective gained chromosomes were expressed less than non-compensated genes thereon ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%